2013
DOI: 10.1136/emermed-2012-202173
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of extracorporeal CPR for in-hospital cardiac arrest secondary to myocardial infarction

Abstract: ECPR may improve survival in cardiac arrest patients who have a ST segment elevation or initial rhythm of VT/VF myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 39 publications
0
46
0
2
Order By: Relevance
“…Finally, 6 studies were included in the metaanalysis comprising 2 260 CA patients, in which 376 and 1 884 patients received ECPR and CCPR respectively. [7][8][9][10][11][12] Those included were all 7-star or 8-star studies according to the NOS grade, suggesting high literature methodology quality. The detailed characteristics of the included studies were shown in Table 1.…”
Section: Eligible Studies and Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 6 studies were included in the metaanalysis comprising 2 260 CA patients, in which 376 and 1 884 patients received ECPR and CCPR respectively. [7][8][9][10][11][12] Those included were all 7-star or 8-star studies according to the NOS grade, suggesting high literature methodology quality. The detailed characteristics of the included studies were shown in Table 1.…”
Section: Eligible Studies and Characteristics Of Included Studiesmentioning
confidence: 99%
“…This procedure demonstrated A predefi ned subgroup analysis was performed according to the location of CA (IHCA or OHCA). Four studies were selected from the subgroup of IHCA [7,8,10,12] and three studies from the subgroup of OHCA. [9,11,12] There was a significant difference in survival to discharge favoring ECPR over CCPR group in OHCA patients (RR 2.69, 95%CI 1.48-4.91, P=0.001) (Figure 4) …”
Section: Subgroup and Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, Ouweneel et al gathered these heterogeneous studies and their meta-analysis brings new insights although no prospective randomized controlled trials exist yet. They selected nine retrospective studies (4,(7)(8)(9)(10)(11)(12)(13)(14), comparing E-CPR vs. conventional CPR (C-CPR), resulting in a total of 3.098 patients (708 ECLS vs. 2.390 control). Outcomes were 30-day survival rate and favorable neurological outcomes [Glasgow-Pittsburgh cerebralperformance categories (CPC) score of 1 or 2] at 30 days evaluated by total cohort and propensity-matched cohort analysis (when available).…”
mentioning
confidence: 99%
“…Indeed, it is worth remembering that PCI is associated with better survival, which is made possible by ECLS for the most severe patients. Lastly, this meta-analysis constantly mixes studies focused on IHCA (4,7,8,10) and OHCA (9-12) with obviously very different survival rates (17). In our opinion, IHCA and OHCA have such distinct presentation, management delays, and outcome that mixing these two populations preclude raising any solid clinical message on E-CPR use.…”
mentioning
confidence: 99%